Stem cells: microenvironment, micro/nanotechnology, and application - Hua Liu (2015)
[Excerpt] Hard tissue damage and loss caused by mechanical trauma, degenerative diseases, infections, tumors, and other diseases exert a profound negative impact on patients’ quality of life and impose a heavy social and economic burden. Currently, tissue engineering is believed to be a promising approach to recover the structural integrity and function of these damaged or diseased hard tissues.[...]